Effect of spent waterglass foundry sand on the performance of MgO-activated slag materials - Hu, Shuimu; Zhang, Wenmin (Frontiers in Materials, 2023)
Spent waterglass foundry sand (SwFS) is a bulk waste of the metallurgical industry containing at least 2-5wt% of waterglass layer without effective utilization.To this end, this paper proposes the disposal of SwFS as fine aggregates for MgO-activated slag materials (MASM). Two SwFSs subjected to different treating temperatures (100 • C and 800 • C) were prepared to investigate their effects on the fluidity, compressive strength, pore structure and micromechanical properties of MASM. The experimental results showed that the coated waterglass of SwFS played an important role in affecting the performance of MASM mortars. For SwFS subjected to 100 ℃, the coated waterglass could be partially dissolved and released into the surrounding paste to activate slag along with MgO. Compared to the group without SwFS, the resulting compressive strength (MPa) of mortars with SwFS was increased by 33.6-74.1% at all ages, and the average elastic moduli (GPa) of C-A-S-H was increased by 19.6%. In contrast, for SwFS subjected to 800 ℃, the coated waterglass can be hardly dissolved, which induced a complex interface in the